A Dramatic Response of a Thyroid Lymphoma to R-CHOP Chemotherapy Reversing Mechanical Airway Obstruction and Respiratory Failure - Zeinab Alnahas; Mohamad H. Horani (Case Reports in Endocrinology)
Primary thyroid lymphoma is an extremely rare thyroid malignancy that usually occurs in patients with preexisting Hashimoto thyroiditis and commonly presents in older women. The most common type is non-Hodgkin’s lymphoma of B-cell origin, particularly diffuse large B-cell lymphoma (DLBCL), which is primarily treated with chemotherapy and radiotherapy. We reported an 83-year-old woman with a past medical history of hypothyroidism who suffered dysphagia and dyspnea secondary to a large thyroid mass. Her CT neck scan showed an enlarged thyroid mass with pathological cervical lymphadenopathy and marked tracheal narrowing. The ultrasound-guided biopsy confirmed the diagnosis of DLBCL of the thyroid. A few days later, she experienced respiratory distress and failure that required endotracheal intubation and mechanical ventilation. She was not considered for tracheostomy or surgical interventions, and after discussion with her family, the decision was made to start R-CHOP therapy (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone) which resulted in a marked reduction of the thyroid size and reversal of the mechanical airway obstruction, enabling her extubation. This case report demonstrated the dramatic response of a large thyroid lymphoma to R-CHOP therapy, reducing the thyroid size and its fatal obstructive complications, including mechanical airway obstruction, within a few days of the initiation of R-CHOP therapy.